1975
DOI: 10.1111/j.1749-6632.1975.tb25410.x
|View full text |Cite
|
Sign up to set email alerts
|

Α‐fetoprotein Levels in Normal Males From Seven Ethnic Groups With Different Hepatocellular Carcinoma Risks

Abstract: Alpha-Fetoprotein (AFP) levels of 1,335 males (15 years and older) of seven ethnic groups (Chinese, Indians, and Malays from Singapore, Caucasians from Lyon, and Blacks from Nairobi, forest, and the savanna region of the Ivory Coast) were determined by radioimmunoassay. A few elevated levels (up to 30 nanounits/ml) were detected in some normal individuals, especially in the older age-groups. In addition, there was a systematic age-dependency of AFP levels particularly evident in the groups from Singapore-Lyon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…One of those forms, the MZ phenotype, has been found by Clerc et al (1977) to be a risk factor for PLC, whereas others, such as Charlionet et al (1976) and Beaugrand et al (1978), have not found such an association. In the latter group, one can also include Theodoropoulos et al (1976) who, on the other hand, found a positive correlation between "FM" (fast moving) (xi-AT components and PLC.…”
mentioning
confidence: 99%
“…One of those forms, the MZ phenotype, has been found by Clerc et al (1977) to be a risk factor for PLC, whereas others, such as Charlionet et al (1976) and Beaugrand et al (1978), have not found such an association. In the latter group, one can also include Theodoropoulos et al (1976) who, on the other hand, found a positive correlation between "FM" (fast moving) (xi-AT components and PLC.…”
mentioning
confidence: 99%
“…Although highly significant, the low value of the coefficient of correlation (r = 0.3095) seems to indicate that the AFP-age relationship is not strong and can be easily modified by a number of factors. It may be that there were small clinically undiagnosed or undiagnosable pathological alterations of the liver either due to infections or parasitic diseases or to toxic aggressions, especially in the older age groups; in this study however a group of Africans from the Ivory Coast, who were chronically infected with hepatitis B virus, did not show higher AFP levels than the negative controls (29). In each ethnic group there was a tendency for AFP to increase with age and pooling all groups together smoothed the curve.…”
Section: Discussionmentioning
confidence: 60%
“…1) as well as purified AFP and individual normal sera (29). Dilutions of the standard down to 0.25 IU/ml1 gave percent inhibition regularly located on 1 By definition (31) 1 IU of AFP is the amount of AFP which is present in 1.3991 Mg of the lyophilized cord serum preparation constituting the international standard and is equal to 1 (former) nIU (29). When examined by 11 laboratories (30) 1 (present) 1U was found to be worth from 0.54 to 1.81 ng of AFP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the significance of this observation in regard to the presence of racial differences, hepatocarcinogen exposure, or endemic hepatitis remains unclear. After a systematic survey of males from seven populations at apparent different risk for hepatoma development, no conclusive demonstration of an association of elevated AFP concentrations was found, although a slight increase with age was noted [170]. Another study [90] noted a small decrease in the average serum AFP concentration after 60 years of age.…”
Section: Human Hepatocellular Carcinomamentioning
confidence: 99%